Motherhood: A Natural Instinct or a Social Construct? : Motherhood in Chimamanda Ngozi Adichie’s Half of a Yellow Sun - Vo, Kim (My University, 2025)
Inspired by my personal journey as a mother, this thesis analyzes the portrayal of motherhood and the roles of women in Chimamanda Ngozi Adichie’s novel Half of a Yellow Sun through the lenses of Adrienne Rich’s concept of Motherhood and Catherine Acholonu’s Motherism. Complementary theories include African Feminism and Womanism. The aim is to explore how motherhood is depicted as both a natural instinct and a social construct, dynamically shaped by cultural and historical contexts, and to examine the societal expectations and challenges faced by women in post-colonial Nigeria. The research employs content analysis, utilizing sequences from the novel to support the theoretical frameworks. The analysis underscores the dual nature of maternal experiences, revealing that motherhood exists at the intersection of instinct and social influence. This balance is context-dependent, shaped by individual circumstances and broader societal expectations. The study highlights the centrality of women in sustaining life and community during conflict, emphasizing their nurturing, protective, and resilient roles. It also delves into the sacrifices entailed in motherhood and the impact of patriarchal ideologies on women’s identities. The findings suggest that Adichie’s portrayal of motherhood challenges traditional gender roles, presenting it as a fluid and transformative experience that defies binary classifications. Love, tolerance, service, and mutual cooperation emerge as core values of maternal roles, demonstrating their significance beyond biological or societal constructs. The thesis concludes that Half of a Yellow Sun offers a nuanced commentary on gender roles and women's empowerment, inviting readers to reconsider the roles and expectations placed upon women and the recognition of their invaluable contributions.
Keywords: Motherhood, Motherism, Maternal resilience, African Feminism, Womanism, Gender Roles, Post-colonial Nigeria, Chimamanda Adichie, Half of a Yellow Sun (The Sun)